TLR-3 Stimulation Skews M2 Macrophages to M1 Through IFN-αβ Signaling and Restricts Tumor Progression - Vidyarthi, Aurobind; Khan, Nargis; Agnihotri, Tapan; Negi, Shikha; Das, Deepjyoti K.; Aqdas, Mohammad; Chatterjee, Deepyan; Colegio, Oscar R.; Tewari, Manoj K.; Agrewala, Javed N. (Frontiers in Immunology, 2018)
During tumor progression, macrophages shift their protective M1-phenotype to pro-tumorigenic M2-subtype. Therefore, conversion of M2 to M1 phenotype may be a potential therapeutic intervention. TLRs are important pathogen recognition receptors expressed by cells of the immune system. Recently, a crucial role of TLR-3 has been suggested in cancer. Consequently, in the current study we defined the role of TLR-3 in the reversion of M2-macrophages to M1. We analyzed the role of TLR-3 stimulation for skewing M2-macrophages to M1 at mRNA and protein level through qRT-PCR, flow cytometry, Western blotting and ELISA. The effectiveness of TLR-3L stimulation to revert M2-macrophages to M1 was evaluated in the murine tumor model. To determine the role of IFN-αβ signaling in-vitro and in-vivo, we used Ifnar1-/- macrophages and anti-IFN-αβ antibodies respectively. We observed upregulation of M1-specific markers MHC-II and costimulatory molecules like CD86, CD80 and CD40 on M2-macrophages upon TLR-3 stimulation. In contrast, reduced expression of M2-indicators CD206, Tim-3 and pro-inflammatory cytokines was noticed. The administration of TLR-3L in the murine tumor, reverted the M2-macrophages to M1-phenotype and regressed the tumor growth. The mechanism deciphered for macrophage reversion and controlling the tumor growth is dependent on IFN-αβ signaling pathway. The results indicate that the signaling through TLR-3 is important in protection against tumors by skewing M2-macrophages to protective M1-subtype.